A nonparametric approach for evaluating long-term energy policy scenarios: An application to the Greek energy system - George Halkos; Nickolaos G. Tzeremes; Panayiotis G. Tzeremes (Journal of Economic Structures, 2015)
This paper by using Long-range Energy Alternatives Planning System (LEAP) constructs four different renewable energy scenarios for the Greek transport, energy, and industry sectors. By projecting the demand for renewable energy and the associated resulting carbon dioxide emissions up to the years 2020 and 2030, the paper applies in a second stage data envelopment analysis (DEA) evaluating the Greek renewable energy policy. As a result, it provides a quantitative measure for future renewable energy policy evaluation under different renewable energy consumption scenarios. The results reveal that the main challenge for the Greek policy makers will be the energy policies associated with the renewable energy usage of the Greek industry since they are rigid toward the adoption of technologies utilizing renewable energy sources. It appears that under the four different energy policy scenarios, the Greek industry sector will not be able to meet its renewable energy targets set by the Greek government. Finally, the analysis reveals that the renewable energy targets set for 2020 and 2030 can be met for the energy sector. However, the renewable energy targets set for the transport sector can only be met for the year 2030.
Keywords: C60; Q47; Q53; Q58; 330; Climate change; Renewable energy sources; Greek energy system; Linear programming; Nonparametric analysis